Figurative languages in novel: A comparative study between Layla Majnun and Romeo and Juliet Novels - Rebekka Basa Natalia Samosir; Theresia Marini Simanjuntak; Katri Helen Lumban Batu; Kristiani Dewi Zai; Fachri Yunanda, S.S., M.Hum., (English Language Teaching Prima Journal (ELT), 2021)
Abstract : Layla Majnun is one of the works of Nizami and Romeo and Juliet is one of the works of William Shakespeare. both novels are romance tradegy novels. Romance tragedy novels usually use a lot of figurative language to beautify the language. This study aims to describe some of the types of figurative language in the novel Layla Majnun, to describe some of the types of figurative language in the novel Romeo and Juliet, to describe the comparison of the types of figurative languages found in novel Layla Majnun and novel Romeo and Juliet. The data obtained for this study are qualitative data. This means, the data are not in the forms of numeric. The data were discourse, such as dialogues, descriptions, ideas or perspectives. The main data of the study are taken from the tragedy novels. The collected data are mostly in the forms of discourse and dialogues taken from the novels as the writers of the novels often apply figurative languages to express their ideas. There are several figurative languages in the discourse and dialogues obtained from the novels which could be interpreted by using Pragmatics theory to identify the meaning behind them. The results of this study indicate that there are similarities and differences in figurative languages in the two novels. The similarities between the two novels are Personification, Metaphore, Hyperbole, and Simile. The differences between the two novels are: Parable, Embodiment, Cynicism, Repetitive, and Irony. Keywords : Figurative Language, Comparative Study, Layla Majnun Novel, Romeo and Juliet Novel.